Pengaruh Motivasi dan Kompensasi Terhadap Kinerja Karyawan (Studi Kasus pada Karyawan PT.MMC Metal Fabrication) - Rahmatullah, Kamal; Hadi, Sudharto Prawata (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2018)
Performance is the result of function that has a strong connection with the strategic objectives of the organization, customer satisfaction and economic contribution. In implementation, there are often obstacles that reduce consumer satisfaction and increase complaints. In the production department of PT. MMC Metal Fabrication, there are several constraints in employee’s performance, including high number of late employee, low employee’s attendance, and not achieving the target quality of goods produced. This study aims to determine the influence of motivation and compensation on the employees’s performance at PT. MMC Metal Fabrication. The type of research use explanatory research. The sample use 85 respondents in the production department 1 PT. MMC Metal Fabrication. The sampling technique use probability sampling. Data collection techniques use questionnaires, observations, and literature studies. Data analysis techniques use validity test, reliability test, correlation test, simple regression test, multiple linear regression test, t test, and f test with the help of IBM SPSS program (Statistical Product and Service Solutions) version 21.0. Based on the results of the analysis, the conclusion is the influence of motivation and compensation on employee’s performance at PT. MMC Metal Fabrication through simple regression testing produces regression values of 0.588 and 0.466. The advice to the company is to give more rewards and penalties for employees who obey the rules and work according to the company's operational standards, evaluate the compensation given to employees each year, and increase employee’s compensation.